PENGARUH KUALITAS WEBSITE DAN HEDONIC SHOPPING TERHADAP IMPULSE BUYING E-COMMERCE BLIBLI DI SURABAYA - Sri Wisnu Diah I. P; Nuruni Ika Kusuma Wardhani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The rapid development of technology has resulted in changes in consumer behavior from initially choosing to purchase offline face-to-face at physical stores to choosing to purchase goods and services online. This phenomenon has a major impact on human life, namely technology in the field of information and smartphones. Increasing the number of sales of digital goods in Indonesia also indicates an increase in consumer behavior in Indonesia. Therefore the purpose of this observation is to find out and understand how much influence the quality of the website and hedonic shopping have on the impulse buying of Blibi e-commerce in Surabaya. This observation uses a quantitative research method by adopting the SEM analysis technique on the SmartPLS analysis tool. This analysis uses primary data collected by distributing purposive sampling questionnaires to 130 respondents who are the object of research, namely users of the Blibi e-commerce platform in Surabaya. The results showed that website quality had a significantly positive impact on impulse buying at Blibli e-commerce in Surabaya, while hedonic shopping had a negative impact and had no effect.